Effectiveness of Under Basket Shoot Through the Maxex Training Model - Kusuma, Dadang Warta Candra Wira; Asmawi, Moch.; Tangkudung, James (International Journal for Educational and Vocational Studies, 2019)
The purpose of this study is to create a draft training shooting model in basketball games and to improve the athletes ability of basketball shooting. This research is mixed-method with research and development (R&D) design. The subject of this research is university player level in Mataram. The formula of t is used with randomized pretest-posttest control groups design. The result of research is creating model of shooting training in basketball games. Thus, the result of data analysis shows that the value of t-test is 11,749 and t-table is 1,729 it means that t-test is higher than t-table (t-test > t-table). The data analysis shows that there is significant effect of shooting training in basketball games and can enhance the players ability.